(untitled) (Research, Society and Development, 2020)
People with celiac disease have difficulties in adopting a completely gluten free diet with nutritional quality. Thus, the aimed of this study to produce gluten free cookies enriched with prebiotic fibers and containing different flaxseed flour concentrations in partial replacement of rice flour. For that, four treatments were prepared with concentrations of 5%, 10%, 15% and 20% of flaxseed flour. The analysis of technological characteristics, color and sensory evaluation were carried out. The flaxseed flour addition 15% decreased (p<0.05) the technological characteristic of increased diameter. For the color data, the lightness was lower (p<0.05) in the formulations with 10, 15 and 20% of flaxseed flour. As for the redness, formulations with 15 and 20% of flaxseed had higher (p<0.05) values when compared to that with 5%. For yellowness, the highest values were for formulations containing 15 and 20% flaxseed. Thus, flaxseed flour gave the cookies a darker color. This darkening has increased consumer acceptance. The terms evaluated by the just-about-right scale, had higher percentages in the just-about-right region: color (68%), flaxseed flavor (58%) and crispness (71%). For purchase intention, all formulations had higher percentages in the region of purchase, with emphasis on the one with 20% linseed (74%). Thus, all cookie formulations were well accepted, with emphasis on the formulation with 20% flaxseed flour.